2020
DOI: 10.1021/acs.est.0c00620
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Fractionation of Substituted Benzene Analogs during Oxidation with Ozone and Hydroxyl Radicals: How Should Experimental Data Be Interpreted?

Abstract: Oxidative processes frequently contribute to organic pollutant degradation in natural and engineered systems such as during the remediation of contaminated sites and in water treatment processes. Because a systematic characterization of abiotic reactions of organic pollutants with oxidants such as ozonation or hydroxyl radicals by compound-specific stable isotope analysis (CSIA) is lacking, stable isotope-based approaches have rarely been applied for the elucidation of mechanisms of such transformations. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Consequently, further reactions with transformation products are expected, such as with muconic acid, which has an apparent second-order rate constant for the reaction with ozone that is one order of magnitude higher than for phenol at pH 3 (k = 1.3 × 10 4 M −1 s −1 (muconic acid) vs k = 1.5 × 10 3 M −1 s −1 (phenol)). 6,49 Under these conditions the higher H 2 O 2 yields (33%) compared to pH 7 (17%) is caused by H 2 O 2 formation by a Criegee-type mechanism from muconic acid (19). Potential H 2 O 2 formation with concomitant benzoquinone formation is only minor (15% benzoquinone yield at pH 3 in % of consumed O 3 5 ).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consequently, further reactions with transformation products are expected, such as with muconic acid, which has an apparent second-order rate constant for the reaction with ozone that is one order of magnitude higher than for phenol at pH 3 (k = 1.3 × 10 4 M −1 s −1 (muconic acid) vs k = 1.5 × 10 3 M −1 s −1 (phenol)). 6,49 Under these conditions the higher H 2 O 2 yields (33%) compared to pH 7 (17%) is caused by H 2 O 2 formation by a Criegee-type mechanism from muconic acid (19). Potential H 2 O 2 formation with concomitant benzoquinone formation is only minor (15% benzoquinone yield at pH 3 in % of consumed O 3 5 ).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Compound-specific isotope analysis (CSIA) offers complementary avenues to elucidate reaction mechanisms of organic chemicals during water treatment based on the evaluation of the natural abundance of the stable isotope composition of reaction products. Previous studies have used CSIA to study the formation of N -nitrosamines upon chloramination of various N -containing precursor compounds and have found that sequences of reactions and their isotope effects can lead to characteristic isotopic compositions. Upon chloramination, 13 C/ 12 C and 15 N/ 14 N ratios in N -nitrosamines are indicative of a specific formation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was challenging to accurately characterize the plant transformation of organic pollutants based on concentrations and products alone. Compound-specific stable isotope analysis (CSIA) is a promising method to characterize the transformation of organic pollutants independent of concentration changes, and different transformation processes was associated with different isotope fractionation effects. Chemical bonds with lighter isotopes in the reaction sites react slightly compared to those with heavier isotopes, leading to the enrichment in heavier isotopes in residual fractions, known as isotope fractionation. It was reported that distinct transformation processes comprised different modes of chemical bond cleavage and thus were associated with specific stable isotope effects. , In addition, the physical processes were unable to cause the detectable changes in stable isotope compositions of organic pollutant. , Therefore, CSIA was successfully applied to investigate the chemical and microbial transformations of PBDEs in the environment. ,, However, the information on the stable isotope effects of organic pollutants during the transformation in plants was very limited.…”
Section: Introductionmentioning
confidence: 99%